ALL CALLED TO THE BANQUET: A RE-EVALUATION OF WHO IS INVITED TO RECEIVE THE BODY AND BLOOD OF CHRIST AND WHY - Candace McLean (Asian Horizons, 2015)
The celebration of the Eucharist is the very summit of the Roman Catholic Church’s liturgical life. While the Eucharist as sacrifice has been emphasized almost exclusively until recent times among Catholics, this is not the only way of speaking about or envisioning what happens when the Body of Christ gathers to share bread and wine, his body and blood, “in memory” of Christ. This paper will explore the various options for depicting the Eucharist, arguing that recovering the models of sacred, covenant meal, and healing “food for the journey” for all who are suffering from the effects of sin, provide the opportunity for the Church to expand hospitality to any person who feels compelled to receive the sacrament. Despite the historical precedent for excluding from Eucharistic reception anyone who is not in full agreement with the Bishop of Rome — thereby making reception of the Eucharist a sign of extant communion among those partaking of it — the efficacy of the sacrament to create or bring to life what it signifies is better suited to reconciling groups that are divided and transforming communities from within. Instead of reinforcing the entrenched, dominant positions only, the invitation to universal reception of the Eucharist allows for the presence of the marginalized, dissenting, and prophetic voices in the summative celebration of thefaith. This results in the welcoming of difference and distinction ritualistically, while preserving unity, which can then emerge more effectively in all areas of Church life.